PENGARUH KEDALAMAN KOLEKTOR TERHADAP PENEMPELAN SPAT TIRAM (Crassostrea sp.) - Fitria Rahmayanti (Universitas Teuku Umar, 2017)
The research was conducted on January 2011 for fourteen days in Krueng Cut River Aceh Besar District. The objective of this study was to determine the effective depth of oyster spats attachment. It used Completely Randomized Design (CRD) with 4 treatment and 3 replication for each treatment and used asbestor as the collector. The collectors depth for A, B, C and D treathment were 30 cm, 60 cm, 90 cm, and 120 cm respectively that measured from the water substrate. Data was analysed by MANOVA (Multivariate Analysis of Variance) used SPSS 17.0. The result showed that the averages of oyster spats attatchment were 86, 98, 35 and 6, respectively. There is tendency that depth collector could affect oyster spats attatchment.